Solar axion production and detection mechanisms - Özuğurel, Umut Deniz. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Production mechanisms of the axion particle in the Sun as well as the detection principle and the data analysis methods that the CAST experiment is based on are reviewed. It is shown that the solar axion production can be explained both by the Primako e ect with a reduced decay width due to plasma screening e ects and by the electromagnetic plasma excitations up to a momentum limit. The analysis of CAST data which results in an upper limit on the axion-photon coupling constant for a range of axion mass is explained in connection with the solar axion ux and the detection principle. Additionally, technical details about CAST is given. Finally, a survey on data collected during the rst part of the second phase of CAST is presented.
Keywords: Axions.